2017
DOI: 10.11591/ijpeds.v8.i1.pp344-359
|View full text |Cite
|
Sign up to set email alerts
|

A New Structure of Dynamic Voltage Restorer Based on Asymmetrical 􀄫-source Inverters to Compensate Voltage Disturbances in Power Distribution Networks

Abstract: As a consequence of sensitive, diverse and complex loads in today's distribution networks, improving power quality in distribution systems has attracted great attention. Power quality issues involve voltage sags, transient interrupts and other distortions in sinusoidal waveforms. Enormous methods have been proposed for power quality modification. One of the methods by which power quality problems might be addressed is to apply power electronic devices in the form of custom power devices. One of such devices is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, cos(2 π n f T S k) , sin(2 π n f T S k) are also known. We want calculate a n , b n and v DC [31]. It is observed that number of unknowns is 2N + 1 and that N is the number of harmonics (or the last order harmonic in voltage).…”
Section: Algebraic Methods For Calculation Of Harmonicmentioning
confidence: 99%
“…Thus, cos(2 π n f T S k) , sin(2 π n f T S k) are also known. We want calculate a n , b n and v DC [31]. It is observed that number of unknowns is 2N + 1 and that N is the number of harmonics (or the last order harmonic in voltage).…”
Section: Algebraic Methods For Calculation Of Harmonicmentioning
confidence: 99%
“…This phenomenon has another influence on the operation of the application; In addition, it has a direct influence on the supply of sensitive loads. Finally, this has an impact on the electrical power available in the installation because there is overconsumption due to harmonics [4,5]. The serial active filter (SAPF) is used and implanted between the delivery point (PCC) and the load to be protected.…”
Section: Introductionmentioning
confidence: 99%